2019
DOI: 10.1101/545806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbiota imprint gut–intrinsic neuronal programming and sympathetic activity

Abstract: P.A.M.), mucida@rockefeller.edu (D.M.) 15 16 Gut-brain connections monitor the intestinal tissue and its microbial and dietary content 1 , 17 regulating both intestinal physiological functions such as nutrient absorption and motility 2-4 , and 18 brain-wired feeding behaviour 3 . It is therefore plausible that circuits exist to detect gut microbes 19 and relay this information to central nervous system (CNS) areas that, in turn, regulate gut 20 physiology 5 . We characterized the influence of the microbiota on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…To address this question interbred a pan-neuronal Cre reporter mouse, Snap25 Cre , with Rpl22 lsl-HA (RiboTag) mice (Sanz et al, 2009), which express a hemagglutinin (HA)-tagged ribosomal subunit 22. Immunofluorescence (IF) analysis of HA+ cells in the myenteric plexus confirmed the significant loss of iEANs as initially determined by ANNA-1 staining (Figure 2A, Figure S2A) (Muller et al, 2019). It has been reported that in cases of overt intestinal inflammation, such as colitis, there is indiscriminate loss of iEANs (Mawe, 2015).…”
Section: Enteric Infections Cause Subtype-specific and Caspase 11-depsupporting
confidence: 74%
See 2 more Smart Citations
“…To address this question interbred a pan-neuronal Cre reporter mouse, Snap25 Cre , with Rpl22 lsl-HA (RiboTag) mice (Sanz et al, 2009), which express a hemagglutinin (HA)-tagged ribosomal subunit 22. Immunofluorescence (IF) analysis of HA+ cells in the myenteric plexus confirmed the significant loss of iEANs as initially determined by ANNA-1 staining (Figure 2A, Figure S2A) (Muller et al, 2019). It has been reported that in cases of overt intestinal inflammation, such as colitis, there is indiscriminate loss of iEANs (Mawe, 2015).…”
Section: Enteric Infections Cause Subtype-specific and Caspase 11-depsupporting
confidence: 74%
“…To gain insights into a possible mechanism involved in infection-induced iEAN cell death, we used neuronal-specific cell-sorting independent translating ribosomal affinity purification (TRAP) (Heiman et al, 2014;Muller et al, 2019). We compared iEANs with extrinsic neurons in the nodose ganglia using Snap25 RiboTag mice, which allow neuronal-specific immunoprecipitation of actively translated mRNA.…”
Section: Enteric Infections Cause Subtype-specific and Caspase 11-depmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction builds the basis of a neuro-epithelial circuit to the CNS that senses gut stimuli via glutamate as the main neurotransmitter (45). However, this finding is controversial because another study did not observe direct neuronal contact with epithelial cells (46). Thus, further experiments need to clarify the exact interaction between sensory neurons and epithelial cells.…”
Section: Neuronal Afferent Signals Modulate Tissue Immunitymentioning
confidence: 99%
“…The microbiota inhabit all mammalian body surfaces and play a pivotal role in the education of the host immune system (68). Recent evidence now suggests that the presence of commensal microbiota also shape the neuronal gene programs and eventually the extrinsic sympathetic activity (46,69). Muller and colleagues proposed that the commensal microbiota shape intrinsic enteric-associated neuronal programs (EAN) region-dependent along the intestine, whereas intrinsic EAN are functionally adapted to the specific intestinal region and its associated microbial challenge.…”
Section: The Enteric Nervous System Integrates Signals From Commensalmentioning
confidence: 99%